2021
DOI: 10.3389/fcell.2021.657667
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Prognostic Significance of Somatic Mutation-Derived LncRNA Signatures of Genomic Instability in Lung Adenocarcinoma

Abstract: Background: Lung adenocarcinoma (LUAD) is a highly heterogeneous tumor with substantial somatic mutations and genome instability, which are emerging hallmarks of cancer. Long non-coding RNAs (lncRNAs) are promising cancer biomarkers that are reportedly involved in genomic instability. However, the identification of genome instability-related lncRNAs (GInLncRNAs) and their clinical significance has not been investigated in LUAD.Methods: We determined GInLncRNAs by combining somatic mutation and transcriptome da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…These mechanisms by which lncRNAs regulate DNA repair-associated genes facilitate our understanding of the link between lncRNA and GI. Moreover, several lncRNA signatures have been established for predicting the prognosis of cancer patients (16)(17)(18)(19)(20), whereas the potential biological and clinical significance of GI-associated lncRNAs in PTC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms by which lncRNAs regulate DNA repair-associated genes facilitate our understanding of the link between lncRNA and GI. Moreover, several lncRNA signatures have been established for predicting the prognosis of cancer patients (16)(17)(18)(19)(20), whereas the potential biological and clinical significance of GI-associated lncRNAs in PTC remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies had found that proto-oncogenes and tumor suppressor genes in nearly 20 common malignant tumors, in which Kidney chromophobe (KICH) was the fewest with 2 genes and Uterine Corpus Endometrial Carcinoma (UCEC) were the most with 55 genes (22). Furthermore, genomic instability was widely involved in the diagnosis and prognosis of various malignant tumors, especially esophageal, bladder, breast, and lung cancers (15,17,27,28). Long non-coding RNAs (lncRNAs) were major components of the mammalian transcriptome and played central roles in a variety of cellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic instability plays a key role in the development of cancer. For example, structural changes in proto-oncogenes and tumor suppressor genes may lead to abnormalities in cell functions, including cell growth, cell cycle, cell senescence and apoptosis, cell invasion and metastasis (15)(16)(17)(18). The genomic instabilities of cancer mainly include gene mutation, chromosome rearrangement and aneuploidy (19).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al constructed a global triple network and found that MALAT1 and LINC00943 may be closely related to melanoma occurrence [11]. Bao et al and Geng et al explored lncRNA signatures associated with gene instability in lung adenocarcinoma and breast cancer, respectively [12,13]. Nevertheless, the relationship between lncRNA in melanoma and genetic instability was not discussed in these bioinformatic studies.…”
Section: Introductionmentioning
confidence: 99%